Systematic review: yellow fever control through environmental management mechanisms - Heinz, Sabine; Kolimenakis, Antonios; Horstick, Olaf; Yakob, Laith; Michaelakis, Antonios; Wilson, Michael (Tropical medicine & international health, 2021)
Objective Recent research on mosquito vector-borne diseases points to the possibility for a re-emergence of yellow fever. This study investigated attempts at utilising environmental methods and their efficacy for the control of yellow fever and its main vector, Aedes aegypti. Methods Potentially eligible studies were searched in Cochrane Library (Reviews and Trials), the Global Index Medicus (encompassing thus the African Index Medicus, the Index Medicus for the Eastern Mediterranean Region, the Index Medicus for the South-East Asia Region, the Latin America and the Caribbean Literature on Health Sciences and the Western Pacific Region Index Medicus), Google Scholar, PubMed and Science Direct. Results Of a total number of 172 eligible studies, 20 met the pre-defined inclusion criteria. Two of them provided quantitative assessment on the efficacy of the described water management and house screening methods with a reduction of cases of 98%, and of a reduction of larvae of 100%, respectively. The remaining 18 studies described or recommended the elimination of breeding sites (through water or waste management, unspecified, or house destruction), the use of screens for houses and the improvement of air circulation without providing any data to evidence control effectiveness. Conclusion This systematic review provides evidence on the historical use and the perceived effectiveness of environmental management methods for combatting yellow fever. However, these methods would benefit from further investigation via controlled trials to provide data for efficacy, costs, acceptability and feasibility.
Gesehen am 27.03.2023